Analysis of Factors Associated with Hemodialysis Patient Compliance During the Covid-19 Pandemic - Hidayati, Rahma; Demawan, Agus Citra; Husna, Elfira; Susanti, Evi; Putra, Yuhendri (Jurnal Kesehatan - STIKes Prima Nusantara, 2023)
Background: Undergoing hemodialysis during the pandemic has become a polemic for patients with kidney failure. As one of the groups at risk and susceptible to exposure, concerns about being exposed to the virus and the consequences if not undergoing hemodialysis are difficult choices. For each dialysis session, the patient must be in contact with many people in one room for 4-5 hours. In addition, their travel to and from the hospital, also increase the chance of being exposed to Covid-19. The uncertainty and low predictability of COVID-19 have an impact on patient adherence to hemodialysis. Meanwhile, patients who do not perform routine hemodialysis are also at risk for various complications, decreasing quality of life and the threat of death.Aims: the purpose of this research was to identify the factors related to patient compliances with hemodialysis therapy during the pandemic Covid-19.Methods : This research was a descriptive analytic using a cross sectional design. Number of samples involving 97 people was taken by a technique. Data was collected using a questionnaire and analyzed with multivariate statistics.Results: 52.6% of respondents did not comply with the hemodialysis schedule. The factors related to the non-adherence were education level (p = 0.003), anxiety level (p = 0.002), ease of access to health services (p = 0.00) and family support (p = 0.00).Conclusion: This research concluded that ease of access to health services was the main predictor of patient adherence to hemodialysis during the pandemic Covid-19.